1999
DOI: 10.1097/00005537-199907001-00001
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Pharmacokinetics in the Inner Ear Fluids: An Animal Study Followed by Clinical Application

Abstract: Overall injection of intratympanic corticosteroids for the treatment of hearing loss in inner ear disorders appears to be both safe and highly effective for certain disorders. The concept of this technique is supported by animal experimental data. The findings from the present study warrant further clinical application and experimental investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
566
3
26

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 573 publications
(611 citation statements)
references
References 45 publications
16
566
3
26
Order By: Relevance
“…Systemic corticosteroids, for example, are used in the otologic management of idiopathic sudden and immune-mediated sensorineural hearing losses (e.g., [51][52][53]). Their clinical usefulness, however, is limited by undesirable side effects arising from the high systemic doses required to achieve sufficient cochlear fluid levels of drug to produce the intended inner ear effects [54]. Middle ear application has advantages over systemic drug delivery, in that drugs so applied can reach their desired targets at higher concentrations and with fewer unwanted systemic side effects.…”
Section: Comparison To Other Delivery Methodsmentioning
confidence: 99%
“…Systemic corticosteroids, for example, are used in the otologic management of idiopathic sudden and immune-mediated sensorineural hearing losses (e.g., [51][52][53]). Their clinical usefulness, however, is limited by undesirable side effects arising from the high systemic doses required to achieve sufficient cochlear fluid levels of drug to produce the intended inner ear effects [54]. Middle ear application has advantages over systemic drug delivery, in that drugs so applied can reach their desired targets at higher concentrations and with fewer unwanted systemic side effects.…”
Section: Comparison To Other Delivery Methodsmentioning
confidence: 99%
“…Substances have been shown to enter scala tympani and from there are distributed in the inner ear (Goycoolea, 2001). Recent pharmacokinetic studies have shown that substances applied locally to the RWM produce significantly higher drug levels in the inner ear fluids compared to systemic applications (Bachmann et al, 2001;Chen et al, 2003a;Parnes et al, 1999). Thus, applying drugs locally may avoid potential systemic complications and side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Parnes et al [20] in a well-designed animal study, compared the concentration of hydrocortisone, methylprednisolone, and dexamethasone in cochlea fluids after intravenous and topical administration. Intratympanic administration resulted in higher endolymph and perilymph levels.…”
Section: Discussionmentioning
confidence: 99%